Comparative Evaluation of Electrochemiluminescence and Chemiluminescence Microparticle Immunoassays for Anti-Hepatitis C Virus (HCV) Detection - Phey Liana; Mita Al Maida; Gita Dwi Prasasty; Desi Oktariana; Tungki Pratama Umar (Fakultas Kedokteran Universitas Sriwijaya, 2024)
Introduction. Anti-hepatitis C virus (HCV) testing is an immunological analysis designed to identify the presence of antibodies against the HCV antigen. This investigation is typically conducted using the chemiluminescence immunoassay (CLIA) technique, which yields precise results. Current research attempts to evaluate the outcomes of the anti-HCV test utilizing the Chemiluminescence Microparticle Immunoassay (CMIA) and the Electrochemiluminescence Immunoassay (ECLIA) approaches. Methods. This cross-sectional study comprised 63 serum samples collected via consecutive sampling. The acquired data were subjected to statistical analysis utilizing Cohen's Kappa agreement test. Results. Both immunoassay methods yielded identical results, indicating four reactive samples out of 63, equating to 6.35%. The agreement test result for the anti-HCV test was κ=1.000, signifying an almost perfect level of agreement. Conclusion. The anti-HCV assessment utilizing CMIA and ECLIA methodologies demonstrated near-perfect agreement. This signifies that these two procedures can be employed in clinical laboratories concurrently or interchangeably for the test.